Studi Kelongsoran di Desa Balesari dan Desa Kembangkuning dengan Menggunakan Metode Empiris dan Software Rocscience Slide 6.0 - Ahmad Muhammad Munif; Dwi Sat Agus Yuwana; Arrizka Yanuar Adipradana (Universitas Tidar, 2021)
Landslides are natural disasters that occur in Indonesia. According to data from the BPS of Magelang Regency in 2018, Windusari District is one of the districts where landslides have occurred, which was recorded 13 times in the last 2 years. One of the villages prone to landslides is in Balesari and Kembangkuning villages. so that anticipation is needed, one of which is by analyzing the stability of the slopes in the village.